Does my professor think my ability can change? Students' perceptions of their STEM professors' mindset beliefs predict their psychological vulnerability, engagement, and performance in class - Muenks, Katherine; Canning, Elizabeth A; LaCosse, Jennifer; Green, Dorainne J; Zirkel, Sabrina; Garcia, Julie A; Murphy, Mary C (Journal of experimental psychology. General, 2020)
Two experiments and 2 field studies examine how college students' perceptions of their science, technology, engineering, and mathematics (STEM) professors' mindset beliefs about the fixedness or malleability of intelligence predict students' anticipated and actual psychological experiences and performance in their STEM classes, as well as their engagement and interest in STEM more broadly. In Studies 1 ( = 252) and 2 ( = 224), faculty mindset beliefs were experimentally manipulated and students were exposed to STEM professors who endorsed either fixed or growth mindset beliefs. In Studies 3 ( = 291) and 4 ( = 902), we examined students' perceptions of their actual STEM professors' mindset beliefs and used experience sampling methodology (ESM) to capture their in-the-moment psychological experiences in those professors' classes. Across all studies, we find that students who perceive that their professor endorses more fixed mindset beliefs anticipate (Studies 1 and 2) and actually experience (Studies 3 and 4) more psychological vulnerability in those professors' classes-specifically, they report less belonging in class, greater evaluative concerns, greater imposter feelings, and greater negative affect. We also find that in-the-moment experiences of psychological vulnerability have downstream consequences. Students who perceive that their STEM professors endorse more fixed mindset beliefs experience greater psychological vulnerability in those professors' classes, which in turn predict greater dropout intentions, lower class attendance, less class engagement, less end-of-semester interest in STEM, and lower grades. These findings contribute to our understanding of how students' perceptions of professors' mindsets can serve as a situational cue that affects students' motivation, engagement, and performance in STEM. (PsycInfo Database Record (c) 2020 APA, all rights reserved).